2000
DOI: 10.2337/diacare.23.7.905
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of infants of mothers with type 1 diabetes: evidence for hereditary and nonhereditary transmission of diabetes and precursors.

Abstract: OBJECTIVE -To estimate the impact of type 1 diabetes during pregnancy on transgenerational genetically caused and/or fuel-mediated amplification of types 1 and 2 diabetes and to estimate the impact of elevated amniotic fluid insulin levels. RESEARCH DESIGN AND METHODS-A total of 75 white offspring of type 1 diabetic mothers and 49 control subjects of similar age and pubertal stage were examined at 5-15 years of age. All offspring had an oral glucose tolerance test. Glucose, insulin, and C-peptide were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 31 publications
(44 reference statements)
6
109
1
4
Order By: Relevance
“…Given the mean age at diagnosis of diabetes in these women (12 years) and the fact that the majority were treated with insulin, we can assume that most of these women had type 1 diabetes. Studies to date that have examined the association of existing maternal type 1 diabetes with future offspring BMI or other markers of adiposity have produced varied results, with some showing greater BMI/adiposity in offspring of such mothers [30,33] and others, like ours, showing no association [34,35]. This variation could be due to small sample sizes in all of these studies, the number of mothers with existing diabetes in each study being 17 [35], 26 (our study), 61 [34], 75 [33] and 160 [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the mean age at diagnosis of diabetes in these women (12 years) and the fact that the majority were treated with insulin, we can assume that most of these women had type 1 diabetes. Studies to date that have examined the association of existing maternal type 1 diabetes with future offspring BMI or other markers of adiposity have produced varied results, with some showing greater BMI/adiposity in offspring of such mothers [30,33] and others, like ours, showing no association [34,35]. This variation could be due to small sample sizes in all of these studies, the number of mothers with existing diabetes in each study being 17 [35], 26 (our study), 61 [34], 75 [33] and 160 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date that have examined the association of existing maternal type 1 diabetes with future offspring BMI or other markers of adiposity have produced varied results, with some showing greater BMI/adiposity in offspring of such mothers [30,33] and others, like ours, showing no association [34,35]. This variation could be due to small sample sizes in all of these studies, the number of mothers with existing diabetes in each study being 17 [35], 26 (our study), 61 [34], 75 [33] and 160 [30]. In addition to these studies, a recent study demonstrated that the adult offspring of mothers with existing type 1 diabetes during their pregnancy (n=15) had similar mean BMI, waist/hip ratio and total fat mass to offspring whose fathers had type 1 diabetes (n=15) [36].…”
Section: Discussionmentioning
confidence: 99%
“…As the maternal and fetal glucose pools are in equilibrium [3], with a rapid transfer of glucose to the fetus according to maternal glucose concentration [4], maternal hyperglycaemia is associated with an adverse pregnancy outcome, most commonly fetal growth acceleration and increased risk of large-for-gestational-age offspring [5][6][7]. This remains the most common complication of pregnancy in type 1 diabetes [8][9][10] and confers immediate risks of delivery complications and neonatal hypoglycaemia in addition to the longer-term risks of insulin resistance, obesity and type 2 diabetes [11][12][13]. After digestion, monosaccharides are transported into the portal vein, where the systemic appearance of glucose is determined by the balance between hepatic extraction and release into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects of maternal undernutrition, there is a growing wealth of experimental evidence revealing that maternal obesity and high fat diets lead to the predisposition for chronic metabolic deficiencies in offspring. For example, maternal high fat diets have thus far been associated with life-long hyperglycemia, insulin resistance, increased fat deposition, and obesity in offspring [53]. In certain studies, independent maternal obesity or diabetes status, maternal high fat diet during pregnancy alone, has led to diabetes related conditions in offspring such as impaired glucose tolerance of the B-cells and impaired insulin secretion of the pancreas [54].…”
Section: Early Life Programming For Disease Susceptibilitymentioning
confidence: 99%